29.9%-efficient, commercially viable perovskite/CuInSe2 thin-film tandem solar cells - Liang, Haoming; Feng, Jiangang; Rodríguez-Gallegos, Carlos D.; Krause, Maximilian; Wang, Xi; Alvianto, Ezra; Guo, Renjun; Liu, Haohui; Kothandaraman, Radha Krishnan; Carron, Romain; Tiwari, Ayodhya N.; Peters, Ian Marius; et al. (Joule, 2023)
Despite the ease of fabrication and no current matching constraint in mechanically stacked thin-film-based tandem solar cells, both electrical and optical losses still limit the performance of wide-band-gap perovskite semi-transparent solar cells in such tandem devices. The thin-film tandems using both perovskite and CuInSe2 (CIS) have not yet achieved optimal levels for commercial viability. Here, we present novel electrical and optical enhancement approaches to maximize the performance of perovskite front cells. We have introduced new electrical and optical techniques, using methyldiammonium diiodide and adjusting the optical interference spectrum. This resulted in a record efficiency of 20.2% (21.8% by J-V scan) for a semi-transparent perovskite cell and 81.5% average near-infrared transmittance. When paired with a CIS bottom cell, the tandem efficiency reached 29.9%. Techno-economic studies show that these tandems could deliver close to 2,000 Wh/m2 daily for certain locations and offer competitive electricity costs, ranging from 3 to 5 USDcents/kWh within ±30° latitude.
CRIS-Team Scopus Importer:2023-12-01
Keywords: 4-terminal tandem devices; carrier management; energy yield analysis; FDTD; finite-difference time-domian simulation; LCOE; levelized cost of electricity analysis; optical management; perovskite solar cells; perovskite/CIS tandem solar cells; techno-economic analysis; V

A digital twin to overcome long-time challenges in photovoltaics - Lüer, Larry; Peters, Ian Marius; Smith, Ana-Suncana; Dorschky, Eva; Eskofier, Björn; Liers-Bergmann, Frauke; Franke, Jörg; Sjarov, Martin; Brossog, Matthias; Guldi, Dirk Michael; Maier, Andreas; Brabec, Christoph (Joule, 2024)
The recent successes of emerging photovoltaics (PVs) are largely driven by innovations in material science. However, closing the gap to commercialization still requires significant progress to match contradicting requirements, such as performance, longevity, and recyclability. In this perspective, we envision the layout of a digital twin for PV materials able to provide the necessary acceleration of innovation. The layout combines machine learning approaches, as performed in materials acceleration platforms (MAPs), with physical models and digital twin concepts used in engineering. This layout will allow the use of high-throughput (HT) experimentation in MAPs to improve the parametrization of quantum chemical and solid-state models. In turn, the improved and generalized models can be used to obtain the crucial structural parameters. HT experimentation will thus yield a detailed understanding of generally valid structure-property relationships. We discuss the current state of the enabling technologies, namely fast scale-bridging surrogate models and large-scale optimization under uncertainty, and identify promising approaches for further development.<br
Keywords: digital twin; emerging photovoltaics; artificial intelligence; multi-scale simulations; optimization; high-throughput methods; materials acceleration platforms

Aerial photoluminescence imaging of PV modules - Doll, Bernd; Wittmann, Ernst; Lüer, Larry; Buerhop-Lutz, Claudia; Hauch, Jens; Brabec, Christoph; Peters, Ian Marius (Conference Record of the IEEE Photovoltaic Specialists Conference, 2023)
On-site imaging of photovoltaic systems requires methods that are high-throughput, low-cost and contact free for commercial relevance. Photoluminescence imaging satisfies these requirements, but it has so far not been used for aerial imaging due to a lack of a drone-mounted system. In this study, we present first results captured by our in-house developed PLAI (photoluminescence aerial imaging) setup. The setup consists of a hexacopter aerial drone equipped with an illumination unit and a near infrared camera. The unit is capable of partially illuminating full size modules at night and capturing the photoluminescence response. We show that the setup can be used to detect and identify defects such as cracks and potential-induced degradation with high levels of confidence.
CRIS-Team Scopus Importer:2024-12-16

Building process design rules for microstructure control in wide-bandgap mixed halide perovskite solar cells by a high-throughput approach - Akhundova, Fatima; Lüer, Larry; Osvet, Andres; Hauch, Jens; Peters, Ian Marius; Forberich, Karen; Li, Ning; Brabec, Christoph (Applied Physics Letters, 2021)
Wide bandgap mixed halide perovskites ABX3, in which X can be I, Br, or Cl, are promising materials to form highly efficient optoelectronic devices, because the optical bandgap can be controlled over a wide range by variation of the halogen composition. However, significant nonradiative losses must be overcome to approach the efficiency limit of single-junction solar cells. Here, we present a high throughput-based investigation of the influence of processing parameters on nonradiative losses in the perovskite bulk. We perform antisolvent crystallization during spin coating and vary the solvent type, its volume, and the temperature of the subsequent annealing step. We use the photoluminescence quantum yield (PLQY) as a proxy to the presence of nonradiative losses and PL spectra as a qualitative probe for sample morphology. Using Gaussian process regression, we find that we can reliably predict PLQY from the PL spectral shape. This means that the PL spectral shape conveys the essential photophysics controlling PL quenching and thus nonradiative charge recombination. In comparison with scanning electron micrographs and x-ray diffraction data, we find that nonradiative losses in polycrystalline perovskite films are caused by increased domain size dispersion. Our method provides a simple and fast structure-sensitive in-line probe for fast morphology optimization in a high-throughput fashion.
CRIS-Team Scopus Importer:2021-06-25

Bypassing the Single Junction Limit with Advanced Photovoltaic Architectures - Lüer, Larry; Peters, Ian Marius; Le Corre, Vincent Marc; Forberich, Karen; Guldi, Dirk Michael; Brabec, Christoph (Advanced Materials, 2023)
Multijunction devices and photon up- and down-conversion are prominent concepts aimed at increasing photovoltaic efficiencies beyond the single junction limit. Integrating these concepts into advanced architectures may address long-standing issues such as processing complexity, microstructure control, and resilience against spectral changes of the incoming radiation. However, so far, no models have been established to predict the performance of such integrated architectures. Here, a simulation environment based on Bayesian optimization is presented, that can predict and virtually optimize the electrical performance of multi-junction architectures, both vertical and lateral, in combination with up- and down-conversion materials. Microstructure effects on performance are explicitly considered using machine-learned predictive models from high throughput experimentation on simpler architectures. Two architectures that would surpass the single junction limit of photovoltaic energy conversion at reasonable complexity are identified: a vertical “staggered half octave system,” where selective absorption allows the use of 6 different bandgaps, and the lateral “overlapping rainbow system” where selective irradiation allows the use of a narrowband energy acceptor with reduced voltage losses, according to the energy gap law. Both architectures would be highly resilient against spectral changes, in contrast with two terminal multi-junction architectures which are limited by Kirchhoff's law.<br

Closing the loop: recycling of MAPbI3 perovskite solar cells - Wu, Zhenni; Sytnyk, Mykhailo; Zhang, Jiyun; Babayeva, Gülüsüm; Kupfer, Christian; Hu, Jin; Arnold, Simon; Hauch, Jens; Brabec, Christoph; Peters, Ian Marius (Energy and Environmental Science, 2024)
Closed-loop recycling is crucial in the rapidly expanding era of photovoltaic deployment. Yet, the recycling of commercial silicon photovoltaic modules presents challenges due to laborious component separation. In contrast, layers in solution-processed solar cells can be separated with relative ease through selective dissolution. In this study, we report on the recovery of every layer in a planar MAPbI3 perovskite solar cell using a layer-by-layer solvent extraction approach, followed by purification or modification to restore quality. This method potentially allows for up to 99.97% recycled mass, thereby conserving resources and reducing waste. We assessed material quality by substituting each fresh material with its recycled equivalent during solar cell production. Subsequently, solar cells were fabricated with either several or all layers comprising recycled materials. Every combination yielded efficiency comparable to cells constructed exclusively with fresh materials, demonstrating the efficacy of the developed recycling process. Our mass and value analysis highlights ITO glass has the highest recycling priority and the need for circular utilization for by-product chemicals, especially cleaning agents. Techno-economic projections suggest that the proposed recycling procedure has the potential to afford substantial cost savings. In the lab, recycling could reduce material costs by up to 63.7%, in industrial manufacturing by up to 61.4%. A life cycle assessment reveals this recycling method can reduce environmental impacts.
CRIS-Team Scopus Importer:2024-06-07

Cradle to Cradle Recycling of Perovskite Solar Cells - Wu, Zhenni; Babayeva, Gülüsüm; Zhang, Jiyun; Sytnyk, Mykhailo; Hauch, Jens; Brabec, Christoph; Peters, Ian Marius (Conference Record of the IEEE Photovoltaic Specialists Conference, 2023)
Cradle-to-cradle recycling plays an important role in resolving one of the major upcoming challenges for photovoltaics in the energy transition-resource management. As photovoltaic production continues to grow, it absorbs a vast amount of resources. Cradle-to-cradle recycling is essential to keep these resources available perpetually and minimize waste generation. To achieve this, a new design paradigm for solar panels that puts recycling in its center is needed. In this study, we show first results of a perovskite solar cell that was created using such a design paradigm. We created a device with 18.1% efficiency and an architecture that facilitates disassembly of the functional layers. We show that the absorber material, MaPbI3 was used for the test device, can be recycled without causing a loss of solar cell efficiency.
CRIS-Team Scopus Importer:2024-12-16

Dynamics of backsheet-driven insulation issues - Buerhop-Lutz, Claudia; Lüer, Larry; Stroyuk, Oleksandr; Hauch, Jens; Peters, Ian Marius (Solar Energy Materials and Solar Cells, 2023)
To reap in the full benefit of high-efficiency solar cells and modules, the quality of the polymer encapsulant and backsheet (BS) materials is essential. Recent field studies show that early degrading backsheets cause safety issues and inverter shutdowns, resulting in yield losses. The dynamic development of degradation is important but is rarely studied because of the lack of proper datasets with meaningful and sufficient data. We studied inverter data of solar panels with a combined capacity of about 1 MWp for more than nine years including ground impedance (GI), and we labelled BS-types using our in-house identification method. Every inverter was connected to modules with exclusively a single BS-type, namely three-multilayer BSs denoted by their outer air layer: PA (polyamide), FC (fluorinated coating), and PVDF (polyvinylidene fluoride). We present, for the first time, an analysis of the degradation dynamics of GI, using a trained Gaussian Process Regression model. Using this model, we derived key degradation parameters, namely GI loss rates and time points for the onset of degradation. We found that PVDF BSs are associated with very low GI loss rates, while loss rates for PA are threefold higher with an onset at 6.6 year of operation for PA. FC BS-related loss rates were humidity dependent and two times higher those of PA; the onset was determined at 4.9 year of operation.
CRIS-Team Scopus Importer:2023-07-21
Keywords: Backsheet; Degradation rate; Gaussian Process Regression; Insulation resistance; Machine learning

Empowering Photovoltaics with Smart Light Management Technologies - Schuster, Christian Stefano; Crupi, Isodiana; Halme, Janne; Koc, Mehmet; Mendes, Manuel João; Peters, Ian Marius; Yerci, Selc¸Uk (Springer International Publishing, 2022)
The daily Sun supplies the continents of the Earth with four times more energy than humanity consumes in a year. This enormous potential of solar energy to generate clean energy is therefore driving great efforts to replace conventional and unsustainable fossil fuel consumption that damages our climate and our environment. Solar photovoltaic (PV) is emerging as the fastest growing renewable energy technology in the world, yet its share to the electricity production currently is less than 3%. While coal and gas remain key to electricity production, the climate crisis demands a fast transition to a carbon-neutral energy system. In the year 2019, the PV industry produced solar panels with a capacity of about 115 GW. To reach multi-TW levels by 2030, PV production capacity needs to scale at high rates, and continued innovation is necessary. One way to increase production is to reduce silicon wafer thickness, making more cells from the amount of silicon produced. Thinning the cell will not only allow making more of them in less time but will also reduce the cost for a module, and for the electricity it generates. A thinner absorber reduces the absorption of sunlight. To counter this loss, optical concepts are needed. In this chapter, we review the most promising approaches in photonics that have made physically thinner but optically thicker solar cells possible. By enabling thinner solar cells, photonic solutions offer the possibility of efficiency enhancements at lower costs. We will explain their applications, discuss their challenges and estimate their impact on energy yield. Finally, we outline how non-silicon thin-film PV is opening up a plethora of consumer-oriented applications. Since the higher flexibility/bendability of thinner cells broadens their applicability range, thin-film PV will empower our transition to a 100% green society in many aspects of our lives.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Dielectric structures; Diffractive structures; Flexible PV; Light-trapping; Photovoltaics; Plasmonics; Solar energy; Tandem solar cells; Thin-film PV

Evolution of inverter ground impedances for PV modules with various backsheet types - Buerhop, Claudia; Stroyuk, Oleksandr; Pickel, Tobias; Hauch, Jens; Peters, Ian Marius (Progress in Photovoltaics, 2022)
Herein, we present results that emphasize the importance of retaining high insulation resistance in polymer backsheets for the reliable operation of photovoltaic installations. By correlating inverter monitoring data, meteorological data, and spectroscopic information from backsheet materials of photovoltaic modules, we derive performance and degradation rates for inverters connected to photovoltaic modules with several backsheet types. The feasibility of evaluating the degradation status of photovoltaic modules in the field through spectroscopic analysis of the water content in backsheet and encapsulant is demonstrated. We show that an increase in water content is a sign for reduced leakage resistance. Ground impedance was measured alongside relative humidity and temperature for three specific backsheet types. Inverters with polyamide and fluorinated coating/polyethylene terephthalate backsheets showed a significant drop in ground impedance at high humidity, RH > 70%. A loss rate of −2 kΩ/day in ground impedance was found for inverters connected to modules with certain fluorinated backsheets. This value is twice as high as for inverters connected to modules with polyamide backsheets. Time series show that the sensitivity to moisture and water ingress increases with time, especially for modules with polyamide and certain fluorinated backsheets. The worst degradation scenario observed had an annual yield loss of 27% due to inverter outages on humid days. About 25% of inverter trip alerts after 8 years of operation included modules with the specific fluorinated backsheet. In general, the study revealed a distinct backsheet impact on ground impedance and operation of inverters and the resulting yield showing an important role of the choice of polymers for reliable and long-lasting photovoltaic systems.
CRIS-Team Scopus Importer:2022-09-16
Keywords: degradation; ground impedance; insulation resistance; near-infrared spectroscopy

Flexible batch electrodialysis for low-cost solar-powered brackish water desalination - He, Wei; Le Henaff, Anne Claire; Amrose, Susan; Buonassisi, Tonio; Peters, Ian Marius; Winter, Amos G. (Nature Water, 2024)
Globally, 1.6 billion people in rural regions face water scarcity. Expanding freshwater access via brackish groundwater desalination can provide additional resources to address this challenge. In this study, we have developed a time-variant electrodialysis reversal (EDR) technology that flexibly uses available solar energy for desalination. Our proposed photovoltaic-powered desalination system can vary pumping and EDR power to match the availability of intermittent solar power, maximizing the desalination rate. Our results show improved system performance with the direct use of 77% of available solar energy—91% more than in conventional systems—and a 92% reduction in battery reliance. In a village-scale desalination case study in India, these system improvements lead to a 22% reduction in water cost, making the technology competitive with the currently used on-grid, village-scale reverse osmosis systems that are mainly powered by fossil fuels. Future advances could further reduce costs, providing an improved, sustainable solution to water scarcity in remote areas.
CRIS-Team Scopus Importer:2025-04-01

On Module Temperature in Floating PV Systems - Peters, Ian Marius; Nobre, Andre M. (Conference Record of the IEEE Photovoltaic Specialists Conference, 2020)
Conventional wisdom has it that floating PV systems have a performance advantage due to a, typically not further specified, cooling effect of water. But how much does the presence of water really contribute to the cooling of PV panels? In this case study, we explore the temperatures of two PV systems located next to one another at a site in Cambodia. One of these systems is mounted on a roof, and one is floating on a pond nearby. For these two installations, we show simulated and measured temperature data. Our analysis suggests that the presence of water does not have a direct effect of the temperature of the floating installation. Differences in the performance of the two sites are best explained by different cooling due to wind. We additionally observe differences in thermal inertia. Overall, we find that, at least without further measures, water bodies only have an indirect effect on PV panel temperature via other factors such as ambient temperature or wind.
CRIS-Team Scopus Importer:2022-06-05
Keywords: Floating PV; Modelling and Simulation

Optimizing Perovskite Thin-Film Parameter Spaces with Machine Learning-Guided Robotic Platform for High-Performance Perovskite Solar Cells - Zhang, Jiyun; Liu, Bowen; Liu, Ziyi; Wu, Jianchang; Arnold, Simon; Shi, Hongyang; Osterrieder, Tobias; Hauch, Jens; Wu, Zhenni; Luo, Junsheng; Wagner, Jerrit; Berger, Christian; et al. (Advanced Energy Materials, 2023)
Simultaneously optimizing the processing parameters of functional thin films remains a challenge. The design and utilization of a fully automated platform called SPINBOT is presented for the engineering of solution-processed functional thin films. The SPINBOT is capable of performing experiments with high sampling variability through the unsupervised processing of hundreds of substrates with exceptional experimental control. Through the iterative optimization process enabled by the Bayesian optimization (BO) algorithm, the SPINBOT explores an intricate parameter space, continuously improving the quality and reproducibility of the produced thin films. This machine learning (ML)-guided reliable SPINBOT platform enables the acceleration of the optimization process of perovskite solar cells via a simple photoluminescence characterization of films. As a result, this study arrives at an optimal film that, when processed into a solar cell in an ambient atmosphere, immediately yields a champion power conversion efficiency (PCE) of 21.6% with satisfactory performance reproducibility. The unsealed devices retain 90% of their initial efficiency after 1100 h of continuous operation at 60–65 °C under metal-halide lamps. It is anticipated that the integration of robotic platforms with the intelligent algorithm will facilitate the widespread adoption of effective autonomous experimentation to address the evolving needs and constraints within the materials science research community.
CRIS-Team Scopus Importer:2023-11-10
Keywords: closed-loop optimization; efficient and stable devices; machine learning; manufacturing optimization; perovskite thin films; PL characterization; robotic platform

Outdoor photoluminescence of large area photovoltaic modules - Doll, Bernd; Hepp, Johannes; Hoffmann, Mathis; Talkenberg, Florian; Schüler, Renè; Baier, Manuel; Buerhop-Lutz, Claudia; Tegtmeyer, Dirk; Peters, Ian Marius; Hauch, Jens; Brabec, Christoph (Proceedings Volume 11809, Organic, Hybrid, and Perovskite Photovoltaics XXII, 2021)
Cost-effective, fast, and non-destructive, on-site photovoltaic (PV) characterization methods are of interest to PV operators to determine countermeasures against defects causing power loss or against safety problems. Combining the advantages of both methods electroluminescence (EL) and thermography is photoluminescence (PL). With our PL setup, we achieved high resolution luminescence images of large area PV modules without any physical and electrical contact. Defects are recognizable with a high rate compared to indoor EL images at controlled conditions. We analyzed inactive areas, cracks, potential induced degradation, snail trails, EVA degradation, and interconnection failures and compared the PL images with different characterization methods.
Keywords: Luminescene; Solar cells; Electroluminescence; Photovoltaics; Image resolution; Light sources; Safety; Sensors; Silicon; Thermography

Photoluminescence for Defect Detection on Full-Sized Photovoltaic Modules - Doll, Bernd; Hepp, Johannes; Hoffmann, Mathis; Schuler, Rene; Buerhop-Lutz, Claudia; Peters, Ian Marius; Hauch, Jens; Maier, Andreas; Brabec, Christoph (IEEE Journal of Photovoltaics, 2021)
Cost-effective, fast, and nondestructive on-site characterization of photovoltaic plants is required to determine countermeasures against power loss, defects, or safety problems. Methods with small impact on the operation and a high throughput, such as infrared thermography (IR), or methods with high resolution for detailed defect information, such as electroluminescence (EL) imaging, are expedient. To combine high resolution and high throughput, we propose to use photoluminescence (PL) as an outdoor characterization method for full-sized module imaging. With PL imaging as with IR imaging, no electrical contact is necessary, yet image resolution is on par with EL images. Our outdoor PL setup features an excitation source with 18 broadband, white, high power, chip on board LEDs coupled with low-cost short pass filters. This setup is suitable for indium gallium arsenide and silicon detectors. Here, we compare the visibility of common defects, including short-circuited bypass diodes, cracks, potential induced degradation, snail trails, ethylene-vinyl acetate degradation, and interconnection failures, in PL images to that in state-of-the-art imaging techniques IR, EL, and ultraviolet fluorescence. We find that out of these seven defects, five can be detected well, cell cracks under certain conditions, and interconnection failures not at all. We discuss how different techniques are complementary to enable better defect detection.
CRIS-Team Scopus Importer:2021-09-17
Keywords: Cameras; Defect detection; Detectors; fluorescence; Image resolution; Imaging; luminescence; photoluminescence; photovoltaic (PV) systems; Silicon; silicon (Si); Throughput; Tools

Photovoltaic Testing for Energy Yield Predictions with Sensitivity to Spectral Shifts - Looney, Erin E.; Liu, Zhe; Classen, Andrej; Buonassisi, Tonio; Peters, Ian Marius (Conference Record of the IEEE Photovoltaic Specialists Conference, 2020)
Solar spectra change depending on location, weather, and time of day around the world. These spectral variations affect the performance of photovoltaic (PV) cells and modules and are not captured by standard testing procedures. We introduce a method to classify spectra and use this classification to develop a testing procedure to reproduce spectral conditions of locations within various climate zones. With LED solar simulators becoming commercially available and representative sets of outdoor spectra found, the gap between real world outdoor testing and indoor testing is closing. With LED-based testing of CdTe, Si, and GaAs PV cells, we show that the effects of spectral shifts on short circuit current are captured, demonstrating the potential use of this method for more accurate testing of solar modules indoors.
CRIS-Team Scopus Importer:2022-06-05
Keywords: LED solar simulators; solar spectrum; testing standards

Practical limits of multijunction solar cells - Peters, Ian Marius; Rodríguez Gallegos, Carlos David; Lüer, Larry; Hauch, Jens; Brabec, Christoph J. (Progress in Photovoltaics, 2023)
Multijunction solar cells offer a path to very high conversion efficiency, exceeding 60% in theory. Under ideal conditions, efficiency increases monotonically with the number of junctions. In this study, we explore technical and economic mechanisms acting on tandem solar cells. We find that these mechanisms produce limitations that are the more pronounced the greater the number of junction is and, hence, limit the ideal number of junctions, as well as the corresponding efficiencies. Spectral variations induce current losses in series-connected tandem solar cells. For Denver, we find that these losses reduce achievable harvesting efficiencies to 51% for non-concentrated light and that they restrict the ideal number of junctions to less than nine. Independently operated solar cells suffer from optical losses with similar consequences. Even high optical efficiencies of 99% restrict the ideal number of junctions to below 10 and reduce achievable efficiencies by more than 10%. Only architectures with a sequential cell illumination are more resilient to these losses. Restricting available materials reveals that a sufficiently low band gap for the bottom cell of 0.9 eV or below is expedient to realize high efficiencies. Economic considerations show that five junctions or less are economically ideal for most conceivable applications.
CRIS-Team Scopus Importer:2023-05-26
Keywords: multijunction solar cell; solar spectrum; techno-economic modelling

The value of stability in photovoltaics - Peters, Ian Marius; Brabec, Christoph; Sinha, Parikhit; Hauch, Jens (Joule, 2021)
Warranties for photovoltaic modules last 25 years. The same duration is frequently used when predicting economic performance. Yet, many modules still produce more than 80% of their original power after 25 years, and there is no economic reason to retire them. Here, we adopt a different mindset: photovoltaic installations are operated indefinitely with maintenance at regular intervals. We reflect this view in a steady-state economic model. We find that in this view, maintenance gains in value -33% compared with a 30-year lifetime-and time constraints for maintenance are lifted. We also find that stability becomes even more important. Reducing annual degradation from 0.5% to 0.2% entails a 12 ct/Watt cost entitlement, increases the economically useful lifetime by a factor of 1.69, defers end of life by decades, and reduces resources and infrastructure needed for recycling by 40%. We foresee that modules installed today should ideally be operated for 50 years.
CRIS-Team WoS Importer:2022-01-07

The Voltage-Ear – An Anomaly in photovoltaic systems with undersized inverters - Wittmann, Ernst; Buerhop-Lutz, Claudia; Christlein, Vincent; Hauch, Jens; Brabec, Christoph; Peters, Ian Marius (IEEE Photonics Journal, 2024)
This study presents a phenomenon in photovoltaic field installations we call voltage ear. PV installations exhibit the voltage ear under specific conditions where modules generate more power than the inverter can handle. When inverters exceed their power limit it results in inverter clipping, and the solar modules are regulated to operate at a voltage above that at maximum power. This kind of voltage rise leads to a specific pattern in the monitoring data – the voltage ear. In the present study, data from a solar park in France was analyzed. This park featured a high rate of inverter malfunctions, including overheating and fires, resulting in an estimated 5% failure rate and, ultimately, in a complete replacement of inverters. An automated analysis of the monitoring data revealed 32.000 occurrences of excess voltage in 1.65 million data points (2%). Instances of the phenomena were detected and segmented using a K-means sorting algorithm, which yielded a perfect recall value. Analysis of the identified voltage ear conditions showed, that it occurs predominantly during seasons of high irradiance and cool temperatures. Excess voltages of up to 161 V in single strings were observed, increasing the probability for PID and inverter damage. The direct yield loss due to deviation from maximum power point was between 0.02% in January and 0.9% in June. We assume, that the voltage ear is a symptom of system design issues that can result in malfunctioning of inverters and hope that it will be useful as an indicator for identifying design and operation issues.<br
Keywords: Inverters; Ear; Voltage measurement; Monitoring; Voltage control; Temperature measurement; Current measurement; PV field inspection; monitoring data; voltage ear; K-means clustering; inverter failure